Ethnopharmacological uses of fauna among the people of central Punjab, Pakistan - Khan, Abdul Majid; Altaf, Muhammad; Hussain, Tanveer; Hamed, M. Haroon; Safdar, Umaira; Ayub, Amina; Memon, Zaibun-nisa; Hafiz, Adnan; Ashraf, Sana; Amjad, Muhammad Shoaib; Majeed, Muhammad; Hassan, Musheerul; et al. (Frontiers in Veterinary Science, 2024)
Utilize of fauna and fauna-based byproducts in ethnomedicinal usages is a centuries-old human activity that is still practiced in many parts of the world today. This study investigates the use of animal-based traditional medicine by the people of Pakistan's Gujranwala area. Data was gathered from January to September 2019 through interviews. To identify the highly desired species in the area, data on ethnomedicinal applications of animal products were studied using several indices such as RFC, RPL, FL, and ROP. Different body parts of 54 species of animals are used to treat various diseases like skin infection, sexual problems, pain in back bone, joint pain, eye sight, night blindness, enhance immunity and memory, cold, weakness, body pain, burn, small pox, wounds in feet, engulf of poisonous things, pain in muscles, arthritis, diabetes, fever, epilepsy, allergy, asthma, burn, herpes, ear pain, paralysis, cough, swelling, cancer, bronchitis, girls maturity, stomach and antibacterial. Species of fauna noted by the most informers have high "frequency of citation" gains, which ranged from 1 to 77. Black cobra (for eye sight) is noted as the most often used with FC = 77 in Gujranwala, domestic rabbit (for burn) has the second highest value of FC=67, Indus Valley spiny-tail ground lizard (for sexual problems) has the third highest value of FC=66. Passer domesticus and Gallus gallus has the highest ROP value as 99. Our findings provide important preliminary information for the conservation of fauna in Gujranwala, Punjab, Pakistan. Screening these animals for medicinally active compounds might aid in the creation of novel animal-based medications.